Applying Of Information Technologes To Knowledge Control Fron Economic Disciplines (Journal of Information Technologies in Education (ITE), 2009)
In the article basic aspects of introduction of the integrated environment of verification of knowledge of students from economic disciplines are expounded. It is resulted list of the modules of the given environment and classification of assignments in relation to the control of knowledge of students from normative economical disciplines. It is noted advantages of application of information technologies at different types of current and final control of knowledge of students of different forms of teaching.
Keywords: current control of knowledge; distance learning systems; economical disciplines; final control of knowledge; institutes of higher education; tasks; testing